Product Environmental Footprint in the construction sector – Proposal and assessment of a representative product for carbon-reinforced concrete - Pamela Haverkamp; Laura Schmidt; Jana Gerta Backes; Marzia Traverso (Journal of CO2 Utilization)
In this study, a representative product for carbon-reinforced concrete (CRC) in Germany is proposed according to the Product Environmental Footprint (PEF) method by the European Commission. Following the objectives of the PEF method, the main goal is to enhance comparability with other studies and promote transparency regarding the environmental performance of products. A CRC façade panel was chosen as the representative product based on insights from German market statistics and sectorial stakeholders. Furthermore, a PEF study was conducted for the defined product. Based on this study, the main environmental hotspots according to PEF are identified – most relevant impact categories, life cycle stages, processes and elementary flows. For instance, the most relevant impact categories were found to be Human Toxicity, cancer, Climate Change, and Resource Use, fossils. For each of these impact categories the most relevant processes and elementary flows were determined. Moreover, the most relevant life cycle was found to be the raw material extraction and pre-processing. An innovative aspect of this study is related to the calculation of the environmental impacts at the end of life. For the first time, the Circular Footprint Formula introduced in the PEF method is applied in the context of CRC. In this regard, a baseline and an alternative scenario are explored. In general, the outcomes of this study are a first step towards the application of the PEF methodology in the context of CRC and create a basis that fosters comparability and transparency in environmental assessments for CRC.